Considerations on D-mannose Mechanism of Action and Consequent Classification of Marketed Healthcare Products - Scaglione, Francesco; Musazzi, Umberto M.; Minghetti, Paola (Frontiers in Pharmacology, 2021)
Urinary tract infections (UTI) are very common in adult women. Half of all women will have at least one episode of UTI during their lifetime, with 20–40% experiencing recurrent episodes. The majority of UTIs seems to be due to uropathogenic Escherichia coli that invades urothelial cells and form quiescent bacterial reservoirs. Recurrences of UTI is often treated with non-prescribed antibiotics by the patients, with increased issues connected to antibiotics resistance. D-mannose, a monosaccharide which is absorbed but not metabolized by the human body, has been proposed as an alternative approach for managing UTI since it can inhibit the bacterial adhesion to the urothelium. This manuscript discusses the mechanisms through which D-mannose acts and to highlight the regulatory aspects relevant for determining the administrative category of healthcare products placed on the market. The existing literature permitted to conclude that the anti-adhesive effect of D-mannose cannot be considered as a pharmacological effect and, therefore, D-mannose products should be classified as a medical device composed of substances.